Implied physical phenomena of rotating closed-loop pulsating heat pipe from working fluid temperature - Kritsada On-ai (2019)
© 2018 Elsevier Ltd The effects of centrifugal acceleration and heat inputs on physical phenomena inside a rotating closed-loop pulsating heat pipe (RCLPHP) are considered by implying from the temperature variation of the working fluid, that are amplitude and frequency of temperature variations. The higher amplitude and frequency of the temperature imply to the longer vapor plugs and the higher flow velocity, respectively. From the experiments, when centrifugal acceleration increases, the temperature amplitude decreases. The flow pattern changes from the annular flow to the slug flow. The temperature frequency increases, the working fluid flows with a higher velocity. The flow direction changes from an oscillatory flow to a circulatory flow. Therefore, the thermal resistance decreases. Moreover, when the heat input increases, the temperature amplitude and frequency increase. The flow pattern changes from the slug flow to the annular flow with an intermittent liquid slug with higher flow velocity, thus, the thermal resistance decreases.